A DNA Logic Gate Automaton for Detection of Rabies and Other Lyssaviruses. Issue 13 (3rd May 2017) - Vijayakumar, Pavithra; Macdonald, Joanne
Abstract: Immediate activation of biosensors is not always desirable, particularly if activation is due to non‐specific interactions. Here we demonstrate the use of deoxyribozyme‐based logic gate networks arranged into visual displays to precisely control activation of biosensors, and demonstrate a prototype molecular automaton able to discriminate between seven different genotypes of Lyssavirus es, including Rabies virus. The device uses novel mixed‐base logic gates to enable detection of the large diversity of Lyssavirus sequence populations, while an ANDNOT logic gate prevents non‐specific activation across genotypes. The resultant device provides a user‐friendly digital‐like, but molecule‐powered, dot‐matrix text output for unequivocal results read‐out that is highly relevant for point of care applications. Abstract : Mixed‐base molecular logic gate networks enable the development of a diagnostic automaton that can distinguish seven genotypes of the Lyssavirus genus, including the Rabies virus. Results are reported in a user‐friendly dot‐matrix fluorescent text display that is highly relevant for point‐of‐care applications.